2009
DOI: 10.1080/07399330902887582
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal Symptom Experience of Hispanic Midlife Women in the United States

Abstract: Using a feminist approach, we examined the menopausal symptom experience of Hispanic midlife women in the U.S. This was a qualitative online forum study among 27 Hispanic midlife women in the U.S. Seven topics related to menopausal symptom experience were used to administer the 6-month online forum. The data were analyzed using thematic analysis. Four themes were identified: (a) “Cambio de vida (change of life),” (b) “being silent about menopause,” (c) “trying to be optimistic,” and (d) “getting support.” More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 56 publications
1
8
0
3
Order By: Relevance
“…These results are consistent with other studies, where women from different cultures and countries identify with the biological milestone of menopause as a sign of aging [15][16][17][18][19][20][21][22] recognizing aging with positive and negative values. 23 Interestingly, the significance of passing to another stage in other cultures has been a synonym for advancement, as role changes, you have more time 24 and gain respect in society 25 older woman are given a position of having greater wisdom, knowledge and ability to hold their own opinions regarding younger women.…”
Section: Discussionsupporting
confidence: 82%
“…These results are consistent with other studies, where women from different cultures and countries identify with the biological milestone of menopause as a sign of aging [15][16][17][18][19][20][21][22] recognizing aging with positive and negative values. 23 Interestingly, the significance of passing to another stage in other cultures has been a synonym for advancement, as role changes, you have more time 24 and gain respect in society 25 older woman are given a position of having greater wisdom, knowledge and ability to hold their own opinions regarding younger women.…”
Section: Discussionsupporting
confidence: 82%
“…This study was a secondary analysis of a larger study, including both quantitative and qualitative sections, comparing the menopausal symptom experience of four major ethnic groups in the United States through an Internet survey and four ethnic-specific online forums (Im, Lee, Chee, Dormire, & Brown, in press, 2009a, 2009b). Only qualitative data from the four online forums were used for this secondary analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Only qualitative data from the four online forums were used for this secondary analysis. More detailed information on the Internet survey and the ethnic-specific online forums can be found elsewhere (Im et al, in press, 2009a, 2009b). The online forums allowed both asynchronous and synchronous communication, through which potential research participants could be approached in various geographical areas promptly and directly heard about their opinions and experiences (Kollock & Smith, 1999).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Menopausal symptoms are commonly assumed to be universal regardless of ethnicity and culture. However, the experience for Latinas has rarely been studied (Im et al, 2009;Villarruel, Harlow, Lopez, & Sowers, 2002). No studies were found regarding Latinas' experience with breast cancer and CIPM despite the potential negative influence on quality of life that was previously reported in non-Latina Caucasian women (Knobf, 2002).…”
mentioning
confidence: 99%